Temporal Trends in Late Preterm and Early Term Birth Rates in 6 High-income Countries in North America and Europe and Association With Clinician-initiated Obstetric Interventions. Issue 2 (June 2017) - Richards, J.L.; Kramer, M.S.; Deb-Rinker, P.; Rouleau, J.; Mortensen, L.; Gissler, M.; Morken, N.H.; Skjærven, R.; Cnattingius, S.; Johansson, S.; Delnord, M.; Dolan, S.M.; et al.
Abstract : ( JAMA . 2016;316(4):410–419) Late preterm and early term births occurring either spontaneously or through obstetric interventions such as labor induction or cesarean delivery have raised concerns due to the risks of adverse neonatal and childhood outcomes. Hence guidelines in the United States now recommend avoiding nonmedically indicated elective deliveries (labor induction or cesarean delivery) before 39 weeks gestation. This study aimed to evaluate temporal trends since 2006 in late preterm and early term birth rates among 6 countries in North America and Europe, and to determine any association between the temporal trends and changes in clinician-initiated obstetric interventions.